PERANCANGAN SISTEM INFORMASI PADA PT. PRASTY MITRA SOLUSINDO BERBASIS WEB - Rizky Maulana; Mochammad Farid A. S.; Wasis Haryono (CV. Multi Kreasi Media, 2023)
With the development of the era, the use of technology as a means of education and socialization is very important for the community. Therefore the author aims to create a website for PT Prasty Mitra Solusindo so that in the future it can be used for promotional and socialization media. This website design uses the waterfall method. Waterfall is one type of application development model and is included in the classic life cycle, which emphasizes sequential and systematic phases. System analysis is a form of description of an absolute information system into a component to evaluate and identify problems that can later be proposed for improvement. There is an analysis of the current system before the system design is carried out. System analysis contains an explanation of the analysis of processes and systems that are running and an analysis of existing problem solving, which consists of system weaknesses and needs in the system. The existence of an existing website at this PT can facilitate data and information to clients to choose what services are needed. In addition, it can help someone's business related to the digital world including its scope such as marketing, promotion, creativity, product development, technology, and so on. Because by using the website every client from anywhere can see what is in PT. PRASTY MITRA SOLUSINDO.